ANALYSIS OF THE EFFECT OF ADHESIVE SUBSTANCES ON PAPER STRENGTH - Aliyeva, Nargiza (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract. The article analyzes high-strength paper samples in the paper production process containing polyester (lavsan) fiber waste, including the introduction of adhesives into the paper cellulose together with synthetic waste fibers, the influence of the selected adhesives on the physical-mechanical and printing properties of the paper.